Bài 27 : Tìm x Z biết. a) x(x + 2) = 0 e) 7x – 13 = 3^2.4 b) 5 – 2x = -7 f) 155 – 5(x + 3) = 80 c

Question

Bài 27 : Tìm x Z biết.
a) x(x + 2) = 0 e) 7x – 13 = 3^2.4
b) 5 – 2x = -7 f) 155 – 5(x + 3) = 80
c) (x + 3)(x – 4) = 0 g) 119 + 3^3.x = 2^3. 5^2
d) – 32 – 4(x – 5) = 0 h) 3(2x + 1) – 19 = 14

in progress 0
Rylee 1 năm 2021-10-28T20:43:01+00:00 2 Answers 10 views 0

Answers ( )

    0
    2021-10-28T20:44:03+00:00

    a) x (x + 2) = 0

    ⇒ x = 0 hoặc x + 2 = 0

    +, Khi x + 2 = 0

    ⇒     x = 0 – 2

    ⇒     x = -2

    Vậy x = 0 hoặc x = -2 

    b) 5 – 2x = -7

    ⇒ 2 x  = 5 – ( – 7 )

    ⇒ 2 x    = 12

    ⇒  x   = 12 : 2 

    ⇒ x = 6

    Vậy x = 6

    c) (x + 3) (x – 4) = 0

    ⇒ x + 3 = 0 hoặc x – 4 = 0

    +, Khi x + 3 = 0

    ⇒   x  = 0 – 3

    ⇒   x  = -3

    +, Khi x – 4 = 0

    ⇒   x = 0 + 4

    ⇒ x   = 4

    Vậy x = -3 hoặc x = 4

    d) – 32 – 4(x – 5) = 0

    ⇒ 4 ( x – 5 )  = -32 – 0

    ⇒ 4 ( x – 5 ) = -32

    ⇒   x – 5    = -32 : 4

    ⇒ x – 5 = -8

    ⇒x = -8 +5

    ⇒ x = -3

    Vậy x = -3

    e) 7x – 13 = 3² . 4

    ⇒7 x -13 = 9 . 4

    ⇒ 7 x -13 = 36

    ⇒ 7x = 36 + 13

    ⇒ 7x = 49

    ⇒ x  = 49 : 7

    ⇒ x  = 7

    Vậy x = 7

    f) 155 – 5(x + 3) = 80

    ⇒ 5 ( x + 3 ) = 155 – 80

    ⇒ 5 ( x – 3 ) = 75

    ⇒ x – 3 = 75 : 5

    ⇒ x – 3 = 15

    ⇒ x = 15 + 3

    ⇒ x = 18

    g) 119 + 3³.x = 2³ . 5²

    ⇒ 119 + 9 .x = 8 . 25

    ⇒ 119 + 9 x  = 200

    ⇒  9x = 200 -119

    ⇒ 9x  = 81

    ⇒ x = 81 : 9

    ⇒ x = 9

    Vậy x = 9

    h) 3 (2x + 1) – 19 = 14

    ⇒ 3 ( 2x + 1 ) = 14 + 19

    ⇒ 3 ( 2x + 1 ) = 33

    ⇒ 2x + 1 = 33 : 3

    ⇒ 2x + 1 = 11

    ⇒ 2x = 11 – 1

    ⇒ 2x = 10

    ⇒ x = 10  : 2

    ⇒ x = 5

    Vậy x = 5

     

    0
    2021-10-28T20:44:21+00:00

    Đáp án + Giải thích các bước giải:

    Ta có :

    `a,x(x+2)=0`

    `→` \(\left[ \begin{array}{l}x=0\\x+2=0\end{array} \right.\) 

    `→` \(\left[ \begin{array}{l}x=0\\x=-2\end{array} \right.\) 

    Vậy `x∈{0;-2}`

    `b,5-2x=-7`

    `→-2x=-5-7`

    `→-2x=-12`

    `→x=6`

    Vậy `x=6`

    `c,(x+3)(x-4)=0`

    `→` \(\left[ \begin{array}{l}x+3=0\\x-4=0\end{array} \right.\) 

    `→` \(\left[ \begin{array}{l}x=-3\\x=4\end{array} \right.\) 

    Vậy `x∈{-3;4}`

    `d,-32-4(x-5)=0`

    `→4(x-5)=-32`

    `→x-5=-32:4`

    `→x-5=-8`

    `→x=-8+5`

    `→x=-3`

    Vậy `x=-3`

    `e,7x-13=3^{2}.4`

    `→7x-13=9.4`

    `→7x-13=36`

    `→7x=49`

    `→x=7`

    Vậy `x=7`

    `f,155-5(x+3)=80`

    `→5(x+3)=155-80`

    `→5(x+3)=75`

    `→x+3=75:5`

    `→x+3=15`

    `→x=15-3`

    `→x=12`

    Vậy `x=12`

    `g,199+3^{3}.x=2^{3}.5^{2}`

    `→199+27x=8.25`

    `→199+27x=200`

    `→27x=200-199`

    `→27x=1`

    `→x=\frac{1}{27}`

    Vậy `x=\frac{1}{27}`

    `h,3(2x+1)-19=14`

    `→3(2x+1)=14+19`

    `→3(2x+1)=33`

    `→2x+1=33:3`

    `→2x+1=11`

    `→2x=10`

    `→x=5`

    Vậy `x=5`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )